2020
DOI: 10.1017/s2045796020001055
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence and disability-adjusted life years of eating disorders from 1990 to 2017: results from the Global Burden of Disease Study 2017

Abstract: Aim Eating disorders have increasingly become a public health concern globally. This study aimed to reveal the burden of eating disorders at the global, regional and national levels using the Global Burden of Disease (GBD) Study 2017 data. Methods We extracted the age-standardised rates (ASRs) of prevalence and disability-adjusted life years (DALYs) and their 95% uncertainty intervals (UIs) of eating disorders, including anorexia nervosa and bulimia nervosa, between 1990 and 2017 from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 43 publications
2
62
1
1
Order By: Relevance
“…However, the prevalence and DALY rates of BN reached a peak at the age of 30-34 years. This finding is consistent with previous results (19). This may be due to the insufficient treatment of adolescent BN patients by clinical psychiatrists and the poor treatment effect.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the prevalence and DALY rates of BN reached a peak at the age of 30-34 years. This finding is consistent with previous results (19). This may be due to the insufficient treatment of adolescent BN patients by clinical psychiatrists and the poor treatment effect.…”
Section: Discussionsupporting
confidence: 93%
“…However, given the very limited information on this issue, further studies in China are needed to explore the potential reason. The aforementioned study found that the burden of eating disorders increased with the increased SDI at regional levels and the highest burden was observed in the high SDI regions, particularly in Australasia, Western Europe, and high-income North America (19). In general, overweight and obesity are positively correlated with economic levels, globalization, and urbanization; these conditions could increase the risk of eating disorders (39).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Eating disorders are serious psychiatric illnesses with a significant public health impact. 1 All eating disorders are characterized by a combination of disturbances in body image and maladaptive eating behaviors. The most well-characterized are anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED).…”
Section: Introductionmentioning
confidence: 99%
“…A major reason for under-powered studies is difficulty recruiting members of narrowly defined (and therefore small) and often hard to reach or retain populations. Although eating disorders are quite common overall (Burt et al, 2020;Kjeldbjerg & Clausen, 2021;Mitchison et al, 2020;Santomauro et al, 2021;Udo & Grilo, 2018;Wu, Liu, Li, Ma, & Wang, 2020), researchers may find it difficult to recruit specific subgroups (e.g., individuals with anorexia nervosa) within a reasonable timeframe. Any steps researchers can take to harmonize recruitment, assessment, training, or intervention protocols, and to share data will help accelerate discovery.…”
Section: The Sample Size Problemmentioning
confidence: 99%